Merde! Teachings from Russian Art to Organizational Learning - Robinson, Rodrigo; Cassandre, Marcio Pascoal (Organizações & Sociedade, 2019)
To consider the human being in its entirety is to understand it as a spiritual being, which does not separate the existential from the instrumental, which finds and shapes the meanings of what lives in the action can be a path to more adequate responses to the present society (LINCOLN; GUBA, 2006). In this article, we relate concepts and practices in Russian art with Organizational Learning (OL). From Vygotsky’s ideas on Double Stimulation and the Ascending from Abstract to the Concrete, used in learning theories like Cultural-Historical Activity Theory (CHAT), we sought to relate the art’s potential to stimulate and develop man learning as a spiritual being with OL. Art has the possibility of awakening a spiritual force that can move man and awaken him to his role of agency, transforming his life and reality. This relationship is established with the proximity of Vygotsky and Stanislavsky and we use the method of the Russian playwright to propose a draft method that considers art as medicine and cure for organizations to understand the human being in its entirety and to constitute spaces for development.